Three-dimensional wave scattering by a fixed cylindrical inclusion submerged in a fluid medium - Tadeu, A. J. B. (1999)
This paper presents the solution for a fixed cylindrical irregular cavity of infinite length submerged in a homogeneous fluid medium, and subjected to dilatational point sources placed at some point in the fluid. The solution is first computed for a wide range of frequencies and wavenumbers, which are then used to obtain time-series by means of (fast) inverse Fourier transforms into space-time.